New Advances in Biomedical Application of Polymeric Micelles - Figueiras, Ana (2022)
Abstract In the last decade, nanomedicine has arisen as an emergent area of medicine, which studies nanometric systems, namely polymeric micelles (PMs), that increase the solubility and the stability of the encapsulated drugs. Furthermore, their application in dermal drug delivery is also relevant. PMs present unique characteristics because of their unique core-shell architecture. They are colloidal dispersions of amphiphilic compounds, which self-assemble in an aqueous medium, giving a structure-type core-shell, with a hydrophobic core (that can encapsulate hydrophobic drugs), and a hydrophilic shell, which works as a stabilizing agent. These features offer PMs adequate steric protection and determine their hydrophilicity, charge, length, and surface density properties. Furthermore, due to their small size, PMs can be absorbed by the intestinal mucosa with the drug, and they transport the drug in the bloodstream until the therapeutic target. Moreover, PMs improve the pharmacokinetic profile of the encapsulated drug, present high load capacity, and are synthesized by a reproducible, easy, and low-cost method. In silico approaches have been explored to improve the physicochemical properties of PMs. Based on this, a computer-aided strategy was developed and validated to enable the delivery of poorly soluble drugs and established critical physicochemical parameters to maximize drug loading, formulation stability, and tumor exposure. Poly(2-oxazoline) (POx)-based PMs display unprecedented high loading concerning water-insoluble drugs and over 60 drugs have been incorporated in POx PMs. Among various stimuli, pH and temperature are the most widely studied for enhanced drug release at the site of action. Researchers are focusing on dual (pH and temperature) responsive PMs for controlled and improved drug release at the site of action. These dual responsive systems are mainly evaluated for cancer therapy as certain malignancies can cause a slight increase in temperature and a decrease in the extracellular pH around the tumor site. This review is a compilation of updated therapeutic applications of PMs, such as PMs that are based on Pluronics®, micelleplexes and Pox-based PMs in several biomedical applications